The Effects of Trade Liberalization on Productivity and Welfare: The Role of Firm Heterogeneity, R&D and Market Structure - Frank Stähler; Horst Raff; Ngo Van Long (Kiel University, Department of Economics, 2007)
This paper develops an oligopolistic model of international trade with heterogeneous firms and endogenous R&D to examine how trade liberalization affects firm and industry productivity, as well as social welfare. We identify four effects of trade liberalization on productivity: (i) a direct effect through changes in R&D investment; (ii) a scale effect due to changes in firm size; (iii) a selection effect due to inefficient firms leaving the market; and (iv) a market-share reallocation effect as efficient firms expand and inefficient firms reduce their output. We show how these effects operate in the short run when market structure is fixed, and in the long run when market structure is endogenous. Among the robust results that hold for any market structure are that trade liberalization (i) increases (decreases) aggregate R&D for low (high) trade costs; (ii) increases expected firm size if trade costs are high; and (iii) raises expected social welfare if trade costs are low.
Keywords: F12; F15; 330; international trade; firm heterogeneity; R&D; productivity; market structure; Außenhandelsliberalisierung; Produktivität; Wohlfahrtseffekt; Oligopol; Endogener technischer Fortschritt; Forschung; Betriebsgrößenstruktur; Theorie